The Role of Meditation on Mental Health of the Students During Covid-19 - Kumar, B M N (International Research Journal of Ayurveda & Yoga, 2024)
Academic achievement is most often hampered by mental health difficulties. Mental illness can have an impact on students’ motivation, attentiveness, and social connections, all of which are important variables in their academic success. The COVID-19 pandemic has raised attention to the mental health of those who have been impacted. Epidemics are known to amplify or create newstressors, such as anxiety and worry for one or loved ones, restrictions on physical movement and social activities due to quarantine, and abrupt and extreme lifestyle changes. Infection worries, frustration, boredom, insufficient resources, insufficient information, financial loss, and stigma were all recognised stresses in a recent assessment of virus outbreaks and pandemics. Meditation has a number of mental health advantages, including greater attention and concentration, increased self-awareness and self-esteem, reduced stress and anxiety, and the development of kindness.